Membrane Distillation Process - Criscuoli, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The book deals with the latest research on membrane distillation. New membrane and module designs, low-temperature applications, integration with other membrane units and pilot scale investigations are presented and discussed.